FIELD EXPERIENCE REPORT: KANSAS DEPARTMENT OF HEALTH AND ENVIRONMENT (KDHE) - Gasper, Rebecca (My University, 2018)
The main objective for this field experience was to gain a greater understanding of the broad field of public health. This was accomplished through the completion of various tasks related to different areas of public health, including: working with state-level health promotion grant work plans, qualitative and quantitative evaluation of grant deliverables to evaluate progress, and compiling a presentation of resources for selecting strategies for use in future projects. The Capitol Midweek Farmers Market was another key part of this experience, where my tasks included communicating with vendors, recruiting special guests from the local community, and creating various promotional materials. This experience gave me a greater understanding of public health as a field and enabled me to further develop my skills in the public health competencies, particularly communicating public health content and interpreting results of data analysis. Working at the state level also helped me to understand the importance of grant funding and how the health promotion initiatives are translated at a local level. Overall the field experience at KDHE gave me the experience, knowledge, and tools necessary to be a successful public health professional.
Keywords: KDHE; Public Health; physical activity; nutrition